The pattern of delinquency in juveniles and its relationship to family construction: An applied study in The Observation Centre in Riyadh - Alosimi, Maryam Rushed Rashdan (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the pattern of juvenile delinquency and its relationship to the family structure in the observation Centre in Riyadh. To achieve the objectives of the study, the analytical descriptive approach was employed. The study sample consisted of (100) juveniles residing in observation centers in Riyadh. A questionnaire consisting of three domains was employed to collect data. The results of the study revealed that the approval of the study sample on the types of juvenile delinquency patterns most prevalent in observation houses in Riyadh is theft of all kinds, fraud) with an arithmetic mean (3.96), and the lowest of these types is (beating and indecent assault.) with an average (3.78), and the sample approval on the social variables of juvenile delinquency in observation homes in Riyadh was large, and that the most prevalent of these variables were (identifying unhealthy and perverted owners) and least of them (corruption or bad neighborhoods in which the individual lives.). The availability of the characteristics of the family structure of juvenile delinquency was large, and mean of all paragraphs of the axis is (3.62), the standard deviation is (0.904). Moreover, the results revealed that there is a statistically significant correlation between the patterns of juvenile delinquency and the characteristics of the family structure, where the Pearson correlation coefficient (.770), and the significance value (.0000). The study recommended directing families to pay attention to and care for children, and to behave in ethical behaviors because children acquire many behaviors by imitation in the early years of life, especially from parents. The study also recommended giving more attention to young people educationally and not to discriminate between children and give each child his right to love, care and attention.